2022
DOI: 10.3390/biology11111568
|View full text |Cite
|
Sign up to set email alerts
|

A New Fern-like Plant Xinhangia spina Gen. et sp. Nov. from the Upper Devonian of China

Abstract: Palaeozoic fern-like plants show great diversity in their morphology and/or anatomy. Within this group, a novel taxon, Xinhangia spina gen. et sp. nov., is now reported from the Upper Devonian (Famennian) Wutong Formation of Anhui Province, China. The primary and secondary branches are borne alternately and sometimes in a triseriate pattern. Spines are evident on the main axes or stems and on the primary branches. Vegetative ultimate appendages with recurved tips are alternate, usually dichotomous 1–2 times, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The fern-like plants in this research were found from several beds in the Leigutai Member (Figure 1c), suggesting their existence for a long time. Materials from the previous study only contain shoot parts, and elaborate structures such as complete fertile organs attached to branches are preserved [16]. Thus, Xinhangia in both previous and present studies, as well as some other fern-like plants (Figures 6 and S2) from the same bed (Figure 1c, the two lowest vertical red lines), are considered as being autochthonous or parautochthonous for the preservation of roots and/or well-preserved aerial branches.…”
Section: Habitat and Environmentmentioning
confidence: 61%
See 4 more Smart Citations
“…The fern-like plants in this research were found from several beds in the Leigutai Member (Figure 1c), suggesting their existence for a long time. Materials from the previous study only contain shoot parts, and elaborate structures such as complete fertile organs attached to branches are preserved [16]. Thus, Xinhangia in both previous and present studies, as well as some other fern-like plants (Figures 6 and S2) from the same bed (Figure 1c, the two lowest vertical red lines), are considered as being autochthonous or parautochthonous for the preservation of roots and/or well-preserved aerial branches.…”
Section: Habitat and Environmentmentioning
confidence: 61%
“…As previously studied, Xinhangia spina possesses characters including primary and secondary branches arranged in alternate and sometimes triseriate patterns, dichotomous vegetative and fertile ultimate appendages with rare divisions, and stele in a clepsydroid shape [16]. The current plants have characteristics including (1) procumbent, spiny, long and sometimes bifurcated stems, (2) primary branches arranged in alternate and sometimes triseriate pattern (Figure 2a-c,e,g), (3) single dichotomized aphlebia inserted at the bases of primary branches (Figure 4e, arrow 3; Figure 4f, arrow 4; Figure 4h, arrow 2), (4) secondary branches borne alternately (Figure 2a, arrows 3-5; Figure 2g, arrow 7), ( 5) dichotomous vegetative ultimate appendages with recurved tips (Figure 5a-c), ( 6) dichotomous fertile organs terminating in paired sporangia (Figure 5d-g), and (7) clepsydroid-shaped primary xylem surrounded by secondary xylem (Figure 5h,i).…”
Section: Assignment Of the Fern-like Plants From Xinhang Forestmentioning
confidence: 67%
See 3 more Smart Citations